On the Dynamic Transmission of Mean and Volatility across the Arab Stock Markets. (December 2014) - Bouri, Elie; Azzi, Georges
This article applies a multivariate model to uncover the dynamic mean and volatility interdependence across the markets of Morocco, Tunisia, Egypt, Lebanon, Jordan, Kuwait, Bahrain, Qatar, United Arabic Emirates (UAE), Saudi Arabia and Oman from June 2005 to January 2012. Results show that the Arab Middle East and North African equity markets are interconnected by their volatilities and not by their returns, which makes risk reduction possible. Volatility persistence and innovations in one market enclose figures that are valuable to investors and risk managers seeking to predict volatility in other markets. Surprisingly, we find evidence of significant volatility spillover from small to larger markets. JEL Classification: G1, G15, G17, C22, C32